SOLAR PV-DIESEL HYBRID SYSTEM FOR THE NANGA MAN VILLAGE - Wibowo, Dandy Putra; Yusuf, Muhammad Ismail; Hiendro, Ayong (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2024)
PLN finds it difficult to meet the electricity needs of the entire Indonesian population. Therefore, it is necessary to develop and optimize New Renewable Energy (EBT) such as solar energy, ocean energy, geothermal, and hydropower. This research uses secondary data that can be accounted for and uses Homer Energy Modeling software to analyze the use of available energy. This research analyzes the planning of a hybrid power plant that uses diesel and solar to meet energy needs in Nanga Man Village from an economic perspective. From the simulations conducted, the analysis results show that the configuration of solar panels - inverter - grid in the on-grid system results in a total overall cost of Rp8,280,976,634.66.